How to Motivate Nonfamily Members? A Chinese Case in Hangzhou - Fu, Sichun (2011)
Research on employee motivation in organizations has proliferated in contemporary literature. Despite this, many studies on family businesses are based on samples from the United States, and empirical researches based on case studies are still limited. Thus, more international research and in-depth analyses on family business are required. Furthermore, those studies, focusing on how to motivate nonfamily members in family-based firms, have been largely overlooked.